Production of tomato powder from tomato puree with foam-mat drying using green pea aquafaba: drying parameters and bioaccessibility of bioactive compounds - Kilicli, Mahmut; Erol, Kubra Feyza; Toker, Omer Said; Tornuk, Fatih (WILEY, 2023)
Background The purpose of this study was to valorize green pea cooking water (aquafaba) as a foaming agent in foam-mat drying of tomato. For this aim, density of foam-mats (green pea aquafaba+tomato puree) changed between 1.06 and 0.45 g/mL depending on the aquafaba concentration. Foam-mats with 5 mm thickness were dried at 50, 60 and 70 degrees C at 1.3 m/s air velocity. Results The results showed that the porous structure of foams with lower densities resulted in higher drying rates and moisture diffusivities. Redness (a*) value decreased with increasing aquafaba content (p < 0.05). Total phenolic content (TPC) and antioxidant activity (CUPRAC, DPPH and FRAP) of the resulting tomato powders were also determined. Moreover, bioaccessibility of phenolics and antioxidant activities were also determined using in vitro digestion. Conclusions All of the bioactive parameters are positively affected by foam-mat drying process. Using aquafaba as a foaming agent accelerated the drying period and improved bioactive characteristics of the powders. (c) 2022 Society of Chemical Industry.
Keywords: foam-mat drying; tomato powder; green pea aquafaba; bioaccessibility; VITRO GASTROINTESTINAL DIGESTION; PHENOLIC-COMPOUNDS; ANTIOXIDANT ACTIVITY; FOOD; ANTHOCYANINS; POLYPHENOLS; STABILITY; LYCOPENE; QUALITY; VACUUM; Agriculture; Chemistry; Food Science & Technology